2013
DOI: 10.1093/pubmed/fdt117
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease, albuminuria and socioeconomic status in the Health Surveys for England 2009 and 2010

Abstract: A B S T R AC TBackground Renal replacement therapy rates are inversely related to socioeconomic status (SES) in developed countries. The relationship between chronic kidney disease (CKD) and SES is less clear. This study examined the relationships between SES and CKD and albuminuria in England. Conclusions CKD 3-5 and albuminuria were associated with low SES using several measures. For albuminuria this was not explained by known measured causal factors. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…It tends to be diagnosed in the presence of other comorbidities (particularly hypertension, diabetes, and cardiovascular disease), isolated CKD is the exception rather than the rule, and CKD is associated with socioeconomic deprivation 13. Effective identification and management are necessary in order to prevent CKD progression and cardiovascular events, reduce the risks associated with acute kidney injury (AKI), and improve patient safety and medicines management.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It tends to be diagnosed in the presence of other comorbidities (particularly hypertension, diabetes, and cardiovascular disease), isolated CKD is the exception rather than the rule, and CKD is associated with socioeconomic deprivation 13. Effective identification and management are necessary in order to prevent CKD progression and cardiovascular events, reduce the risks associated with acute kidney injury (AKI), and improve patient safety and medicines management.…”
Section: Introductionmentioning
confidence: 99%
“…In developed countries, the prevalence of moderate-to-severe CKD (stages G3–G5) in population-representative surveys is estimated at 5%–6%, depending on the equations used to derive eGFR from serum creatinine 2428. Prevalence increases sharply with age and is higher in lower socioeconomic groups and certain ethnic populations 1,24,2931…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data from US studies indicate that black and Hispanic individuals present worse indicators related to CKD than their white counterparts 27 28. A survey in England found that high albuminuria, but not low eGFR, remained associated with low socioeconomic indicators, after adjustment for ethnicity, lifestyle and clinical variables (obesity, diabetes, hypertension and smoking) 29. Greater prevalence of obesity and uncontrolled hypertension and diabetes among non-white individuals are the most common reasons appointed for racial differences in ACR 30–33.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Cr might be affected by high physical activity level [31]. Socioeconomic status [32], anthropometric measurements [33], and blood pressure [34] were related to renal function and CKD. Moreover, kidney function may be affected by sodium intake [35] and animal protein [36, 37].…”
Section: Discussionmentioning
confidence: 99%